ANALYSIS OF LEGAL PROTECTION OF FULFILLMENT OF CHILDREN'S RIGHTS IN DIVORCE CASES IN MEDAN, NORTH SUMATRA - Mutia Octavia; Henry Aspan; Beby Sendy (CV. RADJA PUBLIKA, 2025)
Divorce can be imagined as very sad when viewed from the perspective of a child's life. After a husband and wife officially divorce, Law No. 35 of 2014, especially Article 14, emphasizes that every child has the right to be raised by their own parents, unless there are valid reasons and/or legal regulations that indicate that the separation is in the best interests of the child and is the last consideration. This study aims to determine the fulfillment and legal protection that children receive in divorce cases. The obligations of both parents that must be fulfilled as regulated in Law No. 35 of 2014, Article 9 concerning child protection, state that when a divorce occurs, parents are still obliged to fulfill the child's rights with full affection. The results of this study were conducted to determine how children's rights are fulfilled in divorce in North Sumatra. This study was conducted with information sources from the Indonesian Child Protection Agency (LPAI) in North Sumatra. The results of this study indicate that with divorce, children's rights have not been fully fulfilled. However, to be able to realize this, awareness of both parents is needed that there are still children's rights that must be fulfilled after a divorce occurs.